2013
DOI: 10.3109/21691401.2012.762370
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide form of PEGylated hemoglobin protects myocardium against ischemia/reperfusion injury in diabetic and normal mice

Abstract: We investigated the pre-clinical utility of carbon monoxide form of PEGylated hemoglobin (PEG-Hb also named SANGUINATE(™)) in myocardial infarction (MI) and in particular the response of diabetic tissues to superimposed ischemia/reperfusion injury. SANGUINATE(™) was evaluated in diabetic and normal mice subjected to 30 min of coronary artery ligation followed by either 48 h or 28 days of reperfusion. Our results demonstrate that SANGUINATE(™) was effective in reducing infarct size when administered either prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…These in vitro findings [12,16] were consistent with the observation that Nielsen et al 4 4 platelet soluble guanylate cyclase activity did not correlate with CO exposure from residential heating of various types [13]. Of interest, an additional, site-directed delivery system of CO described in rodent models includes intravenous administration of COloaded, pegylated hemoglobin [77][78][79]; however, hemostatic effects of this methodology have not been tested. Lastly, in contrast to platelet aggregation studies, determinations of platelet activation by mean platelet volume in healthy volunteers exposed to passive smoking [14], or victims of CO poisoning [17], have demonstrated enhanced activation following exposure to CO.…”
Section: Clinical Preclinical and In Vitro Evidence That Co Is An Ansupporting
confidence: 74%
“…These in vitro findings [12,16] were consistent with the observation that Nielsen et al 4 4 platelet soluble guanylate cyclase activity did not correlate with CO exposure from residential heating of various types [13]. Of interest, an additional, site-directed delivery system of CO described in rodent models includes intravenous administration of COloaded, pegylated hemoglobin [77][78][79]; however, hemostatic effects of this methodology have not been tested. Lastly, in contrast to platelet aggregation studies, determinations of platelet activation by mean platelet volume in healthy volunteers exposed to passive smoking [14], or victims of CO poisoning [17], have demonstrated enhanced activation following exposure to CO.…”
Section: Clinical Preclinical and In Vitro Evidence That Co Is An Ansupporting
confidence: 74%
“…These results were unexpected as a similar, but slightly higher, dose (10 mL/kg IV) of Sanguinate given 20 min after a 2 h period of ischemic stroke improved the 24 h neurologic score in rats (Klaus et al, 2010) and reduced brain infarct size at 24 h (Klaus et al, 2010) and at 3 days (Zhang et al, 2012). Intraperitoneal infusion of Sanguinate (20 mL/kg) at 1 day and 2 day after myocardial infarction in mice reduced plasma troponin-I measured at 48 h (Ananthakrishnan et al, 2013). In all of these studies, the earliest beneficial effect of Sanguinate occurred after 24 h while in our study the observation period was less than three hours.…”
Section: Discussionmentioning
confidence: 51%
“…Plasma viscosity may be important for maintaining shear stress-induced NO production by the endothelium and thus may be another mechanism, in addition to the CO, to promote vasodilation (Tsai et al, 2005). Studies have shown that Sanguinate reduces troponin-I after myocardial infarction in mice (Ananthakrishnan et al, 2013) and reduces cerebral infarct volume in rats (Klaus et al, 2010). Overall, the literature indicates that a treatment regimen, such as administering an HBOC, that increases brain tissue oxygenation without cerebral vasoconstriction could improve long-term mortality and morbidity following TBI.…”
Section: Microvascular Researchmentioning
confidence: 98%
“…In a model of myocardial I/R injury, treatment with CO-releasing compound PEGylated carboxyhemoglobin bovine (PEG-COOH) drastically reduced infarct size and troponin levels in STZ-induced diabetic mice. In mice receiving PEG-COOH during reperfusion only, infarct size was reduced, suggesting CO as a potential therapeutic agent for patients after myocardial infarction (123). In STZ-induced diabetes in rats, induction of HO-1 with hemin, and treatment with CORM-2 to lesser extent, attenuated vascular damage and oxidative stress and improved vascular relaxation compared with nontreated rats (124).…”
Section: Gasotransmitters In Macrovascular Diseasementioning
confidence: 99%